ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN KOPERASI (STUDI KASUS PADA KSP KOPDIT PINTU AIR TAHUN 2017–2021) - Herdi, Hendrikus; Trisyami Irmayati Subu, Fransiska (Program Studi Akuntansi Fakultas Ekonomi dan BisnisUniversitas Nusa Nipa, 2022)
: This study aims to inform the financial performance of KSP Kopdit Pintu Air based on financial ratios. The analysis is carried out by examining financial ratios, namely Liquidity Ratios, Solvency Ratios, and Profitability Ratios. One type of cooperative that is currently developing is a savings and loan cooperative (KSP) which is engaged in fertilizing deposits from members and lending back to members who need financial assistance. For this reason, financial performance needs to be considered carefully, using financial ratios in determining the financial performance of a company or cooperative. Ratio analysis is a technique that shows the relationship between 2 accounting elements that allows business owners to analyze financial performance. This research was conducted at KSP Kopdit Pintu Air. KSP Kopdit Pintu Air is a credit cooperative group. The population used in this study is the financial report of Ksp Kopdit Pintu Air. The sample used in this study is financial ratios, namely the statement of financial position and the report of the remaining operating results at Ksp Kopdit Pintu Air in 2017- 2021. Analysis of the data used in this study by presenting a description of the explanation using the method of calculating financial ratios: Liquidity Ratios, Solvency Ratios, and Profitability Ratios. The results showed that the financial ratios at Ksp Kopdit Pintu Air were still below the standard.